Characterization and modelling of the sound reduction of hemp-clay walls in buildings. (August 2021) - Glé, Philippe; Massossa-Telo, Gaudrey; Hellouin de Menibus, Arthur; Degrave-Lemeurs, Matthias; Gourdon, Emmanuel
Abstract: This paper focuses on the sound reduction of light earth at the wall scale. It aims at gaining knowledge and providing informations to professional building workers to help them in the acoustic optimization of biobased walls. Experimentations have been performed in controlled conditions using the intensimetry method, on 22 different samples to investigate thickness effect, wood frame effect, coating effect together with different light earth implementations (shuttering, spraying). These data were then confronted to two modelling approaches, the mass law estimate and a Transfer Matrix Method computation. It is shown that light earth performance can be satisfactorily predicted, whatever the wall configuration using the Transfer Matrix Method computation with isotropic elastic and porous layers. The study brings finally a good understanding of the physical phenomena occurring in biobased concretes, depending on the presence of coatings. For light earth, it also appears that mass law yields to a good approximation of the single-number rating for some configurations including at least one coating. Highlights: Manufacturing process slightly affects the sound reduction of light earth. Framing and thin skins have limited effects on transmission loss of light earth. Uncoated light earth behaves acoustically as a rigid frame porous layer. Light earth with coating can be modelled with a multilayered elastic solid approach.